1973
DOI: 10.1111/j.1744-7348.1973.tb07309.x
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal control of gas exchange in barley awns

Abstract: SUMMARY The gas exchange of barley ears and awns was measured in the field using a gas analysis system and a diffusion porometer. Awn stomatal resistance decreased with increasing irradiance but to a smaller extent than leaf stomatal resistance. Measurements on ears immediately before and after successively removing awns showed that awn transpiration and photosynthesis were proportional to awn area and that awns accounted for 73% of transpiration by the ear. Although the maximum rates of photosynthesis of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
4
16
1
Order By: Relevance
“…He calculated the abaxial surface of the hypostomatous awns of one ear to be 42 cm 2. Taking this value as representative, maximal awn transpiration determined by Biscoe et al (1973) would amount to 2.8 mg U 2 0 cm 2 h-l, which is of similar magnitude as our measurements. Awn stomata respond to solar radiation (Biscoe et al, 1973) and are probably affected also by other micrometeorological factors and by the ear water status, as can be deduced from the diurnal courses depicted in Figure 7.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…He calculated the abaxial surface of the hypostomatous awns of one ear to be 42 cm 2. Taking this value as representative, maximal awn transpiration determined by Biscoe et al (1973) would amount to 2.8 mg U 2 0 cm 2 h-l, which is of similar magnitude as our measurements. Awn stomata respond to solar radiation (Biscoe et al, 1973) and are probably affected also by other micrometeorological factors and by the ear water status, as can be deduced from the diurnal courses depicted in Figure 7.…”
Section: Discussionsupporting
confidence: 63%
“…Taking this value as representative, maximal awn transpiration determined by Biscoe et al (1973) would amount to 2.8 mg U 2 0 cm 2 h-l, which is of similar magnitude as our measurements. Awn stomata respond to solar radiation (Biscoe et al, 1973) and are probably affected also by other micrometeorological factors and by the ear water status, as can be deduced from the diurnal courses depicted in Figure 7. Patterns of increase and decrease of awn resistances to water vapour transfer were similar to those of the flag leaves and did not simply passively follow the evaporative demands.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, using the projected area underestimates CAI especially of awns. Biscoe et al (1973) found that 73% of ear transpiration may originate from awns and that transpiration was proportional to awn area as calculated from single awn area. They also found a low g value of awns as compared to flag leaves.…”
Section: Discussionmentioning
confidence: 99%
“…In barley, ear carbon exchange, transpiration, and respiration rates peak near anthesis, begin to decline 9 to 12 d after anthesis (DDA), and cease about 30 DDA (Kjack and Witters 1974). Estimates of the contribution made by ear photosynthesis to final grain mass of barley vary from as little as 13 % (Biscoe et al 1973) to as much as 70 % (Thorne 1963). Thus, ear metabolism makes a critical contribution to world food production of C 3 cereals and should not be ignored.…”
Section: Introductionmentioning
confidence: 97%